2022
DOI: 10.3390/vaccines10020230
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccine Refusal among Nurses Worldwide: Review of Trends and Predictors

Abstract: COVID-19 vaccination hesitancy has become a major concern around the world. Recent reports have also highlighted COVID-19 vaccination hesitancy in healthcare workers. Despite media reports and scientific publications, little is known about the extent and predictors of COVID-19 vaccination refusal among nurses. Thus, the purpose of this study was to assess COVID-19 vaccine refusal rates among nurses globally and to explore the reasons for refusal and factors associated with the uptake of the vaccines. A scoping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
143
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(150 citation statements)
references
References 73 publications
5
143
1
1
Order By: Relevance
“…Advantages of online resources and data to support study One of the advantages of data used by the nursing world online is the report by the World Health Organization (WHO) or the World Health Organization that has declared COVID-19 as a global pandemic in mid-March 2020 (Khubchandani et al, 2022). This certainty is very reasonable considering that the spread of cases has reached 118,000 in 114 countries.…”
Section: Resultsmentioning
confidence: 99%
“…Advantages of online resources and data to support study One of the advantages of data used by the nursing world online is the report by the World Health Organization (WHO) or the World Health Organization that has declared COVID-19 as a global pandemic in mid-March 2020 (Khubchandani et al, 2022). This certainty is very reasonable considering that the spread of cases has reached 118,000 in 114 countries.…”
Section: Resultsmentioning
confidence: 99%
“…As a new finding, the theme ‘experiencing the mixed emotions towards jabs’ emerged in the second/third wave. As documented internationally by recent systematic and scoping reviews, 67 , 68 while some nurses have reported being grateful to science for making the vaccine against COVID-19 and not understanding the widespread reluctance of their anti-vax colleagues; others have expressed fear and indecision about its possible adverse effects. Furthermore, if some nurses have lived the vaccination campaign for COVID-19 as a moral obligation and a gesture of social responsibility, others have experienced this vaccine as an imposition, promoting a bioethical debate on its mandatory nature within health organizations.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest vaccine acceptance could be promoted through encouragement from within these relational groups, particularly for non-white racial/ethnic HCWs. Previous studies found that the main reasons for COVID-19 vaccination among HCWs are family, friends, and healthcare workers [46,47] but did not examine whether race and ethnicity modify the motivations.…”
Section: Race/ethnicitymentioning
confidence: 97%
“…A survey of low-income, primarily female, Latino SNAP participants in Southern California found that having children was inversely associated with vaccine refusal while being single, separated/divorced, or widowed, and use of social media platforms was positively associated with vaccine refusal [53]. Themes of protecting family members and the community are present in studies of non-HCWs [17,46,47] and HCWs [54]. Thus, messaging focused on safeguarding vulnerable individuals from similar racial/ethnic backgrounds could provide an opportunity to increase vaccine uptake among HCWs in addition to the general popula-tion.…”
Section: Race/ethnicitymentioning
confidence: 99%